Get A&Wdicted! di Restoran Khas Amerika: Pengaruh Cognitive Learning dan Message Reception and Processing Terhadap Perubahan Sikap Konsumen - Elsye Rumondang Damanik (Bina Nusantara University, 2012)
Article clarified a research on cognitive response effect on cognition, attitude, and purpose. The purpose of this study was to analyze the influence of cognitive learning and a set of message processing system to persuade consumers. Researcher obtained the data and information from literature study, media, and direct observation to A & W Restaurants located at Rawamangun, Kelapa Gading Mall, and Bina Nusantara University. The result shows that human thinking process relates to ego involvement which includes culture and living habit is influential to the way people process the message. Finally, it is concluded that it is important to understand how consumers do message processing in order to make marketers able to determine the right marketing strategy to influence their consumers’ attitudes.